(untitled) (Research Journal of Mathematics & Technology, 2022)
This paper introduces functional programming to the numerical methods community with the aim of popularizing this programming paradigm through a deeper appreciation for function as a mathematical concept and, at the same time, for its practical benefits. The functional language HASKELL is chosen amongst several choices because of its lazy evaluation strategy and high-performance compiler WinGHCi. We demonstrate the elegance and versatility of HASKELL by coding HASKELL programs to implement well-known numerical methods.